Analysis of the probable oil spill scenarios in Laguna Lake using hydraulic modeling - Cruzem, Jazel F.
Laguna Lake is the largest freshwater body in the Philippines. Despite its size however, its average depth is only 2-2.5 meters. Millions of people depend on the lake for food and livelihood. Bounded by 6 provinces, the lake has been valuable for water borne transport. With its various uses, the environmental integrity of the lake has been stressed and threatened. One possible threat is oil spill considering oil transport exists in the lake. A barge carrying a minimum of 300,000 liters of oil travels on the lake to deliver fuel for the operation of the Malaya Thermal Power Plant, a 650-MW power plant in Pilila, Rizal. If oil spill accidentally occurs, it will definitely endanger the lives of humans, including plant and animal communities thriving on the lake. The main objective of this research is to analyze the spreading of oil on the water surface of Laguna Lake for different oil spill scenarios and to create an oil spill risk map based on oil concentration distribution. The results of this study may help in preparing emergency plans, oil spill mitigations and clean-up operations. A 2D hydrodynamic model was created using Delft3D-FLOW. The model was calibrated using lake water level data in 2003 and validated in 2004 using water level and flow velocity intormation. Different oil spill scenarios were simulated by varying the oil spill accident locations for both wet and dry season lake hydrodynamics. The results of the study showed that the rate of spread of the oil spill is faster during wet season. The resulting oil concentration distribution also demonstrated that the highest concentration almost always occur at the Central Bay of the lake, with a concentration value of 0.000285 during dry season and 0.000222 during wet season. The area least affected by oil spill incidents on the other hand is the eastern lobe of the lake having a maximum concentration of3.15x10-7 in dry season and 2.17x10-6 in wet season.